2017
DOI: 10.2967/jnumed.113.129593
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Radionuclide Imaging in Epilepsy, Part 2: Epilepsy Syndromes

Abstract: CE credit: For CE credit, you can access the test for this article, as well as additional JNMT CE tests, online at https://www.snmmilearningcenter.org. Complete the test online no later than March 2020. Your online test will be scored immediately. You may make 3 attempts to pass the test and must answer 80% of the questions correctly to receive 1.0 CEH (Continuing Education Hour) credit. SNMMI members will have their CEH credit added to their VOICE transcript automatically; nonmembers will be able to print out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 76 publications
0
12
0
2
Order By: Relevance
“…Several reviews on PET and SPECT in presurgical evaluation were published during this period [ 31 ▪▪ , 56 ▪▪ – 59 ▪▪ , 60 ▪ ].…”
Section: Reviewsmentioning
confidence: 99%
“…Several reviews on PET and SPECT in presurgical evaluation were published during this period [ 31 ▪▪ , 56 ▪▪ – 59 ▪▪ , 60 ▪ ].…”
Section: Reviewsmentioning
confidence: 99%
“…This result underlines the value of a multimodal neuroimaging evaluation prior to hemispherotomy as already recommended by others. 12,13 Most interestingly, seizure freedom was also achieved in 100% of the patients with unilateral PET despite bilateral MRI (Group AII; Fig. 2) but only in 87.5% of the patients with bilateral PET and unilateral MRI (Group BI; Table 2).…”
Section: Discussionmentioning
confidence: 94%
“…16 PET-based and SPECT-based techniques have also been investigated with respect to their value for both a better delineation of the functional deficit zone prior to surgery and the prediction of possible functional deficits after surgery. 13 The largest outcome study after hemispheric surgery (based on 170 patients) was published in 2013. 15 In this retrospective study, 18 F-FDG PET as well as MRI findings were found to be of prognostic value for postsurgical seizure outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular imaging by positron emission tomography [16] with 11 C-flumazenil (FMZ) has been useful in the assessment of patients having neural damage, including epilepsy, because FMZ binds to the benzodiazepine site of the GABA A receptor complex in humans [17][18][19][20]. We also have investigated neural damage in patients with cerebrovascular diseases using the specific parameter of the binding potential (BP) of FMZ to the GABA A receptor complex in the human brain [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%